2017
DOI: 10.1186/s12874-017-0316-6
|View full text |Cite
|
Sign up to set email alerts
|

Methods for conceptualising ‘visual ability’ as a measurable construct in children with cerebral palsy

Abstract: BackgroundVision influences functioning and disability of children with cerebral palsy, so there is a growing need for psychometrically robust tools to advance assessment of children’s vision abilities in clinical practice and research. Vision is a complex construct, and in the absence of clarity about this construct it is challenging to know whether valid, reliable measures exist. This study reports a method for conceptualising ‘visual ability’ as a measurable construct.MethodsUsing the items from 19 assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The VFCS was developed empirically following a step‐by‐step process to classify visual abilities of children with CP in everyday life. Visual abilities refer to how the child uses vision purposefully to see, direct gaze, recognize, interact with the environment, and explore it . In fact, while measures of visual impairment, at the level of the eye or brain, are valuable and necessary in the diagnosis and management of children with CP, they do not provide information on how visual dysfunction affects daily life, and do not take into account children's abilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The VFCS was developed empirically following a step‐by‐step process to classify visual abilities of children with CP in everyday life. Visual abilities refer to how the child uses vision purposefully to see, direct gaze, recognize, interact with the environment, and explore it . In fact, while measures of visual impairment, at the level of the eye or brain, are valuable and necessary in the diagnosis and management of children with CP, they do not provide information on how visual dysfunction affects daily life, and do not take into account children's abilities.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, while measures of visual impairment, at the level of the eye or brain, are valuable and necessary in the diagnosis and management of children with CP, they do not provide information on how visual dysfunction affects daily life, and do not take into account children's abilities. Although some children with CP may show limited levels of functioning and restricted participation due to their visual impairment, others can rely on their visual abilities to overcome their limitations due to motor impairment …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasticity of the visual system and results of previous studies showed that training can enhance visual function which led to the concept of developing training programs matching the nature and degree of visual dysfunction. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…The work by Baranello et al . to create the VFCS, and the emerging studies of Deramore Denver and her group in Australia to create tools to assess children's visual functioning, complement the few research teams exploring a clinical understanding of the assessment and management of children who grow up with significant challenges in visual functioning …”
mentioning
confidence: 99%